A New Approach to Measuring Local Properties of Preforms Enhanced for Formability - Turk, Mark A.; Cao, Hengli; Thompson, Adam J.; Belnoue, Jonathan P-H.; Hallett, Stephen R.; Ivanov, Dmitry S. (Frontiers in Materials, 2022)
Forming of dry engineering textiles is a quality-critical operation in composites manufacturing. There are various different defect mitigation strategies that have been developed to ensure that material will not wrinkle or fold when depositing and forming. One promising direction is the modification of textile properties in the regions where a defect is likely to form. This can be achieved by the integration of patches: additional materials, such as reactive thermally-conditioned resins, tufted or stitched yarns, thermoplastic films, locally activated binder, etc. This method is simple and effective for a certain class of forming problems. The success of the forming operation depends on the balance of properties between dry and patched materials. At present, there is no clearly established methodology for the characterisation of these formability enhancements. Patches are local and an isolated coupon often cannot be extracted from a hosting fabric. This paper discusses the feasibility of adapting the conventional bias extension test (BET) to extract the shear properties of locally enhanced material. The obtained properties are critical for modelling tools that can inform the optimum patch location and orientation. The suggested approach is practical, simple to implement and proven to provide properties to a reasonable degree of accuracy for non-linear elastic and visco-elastic patch behaviours.